VALIDITAS DAN RELIABILITAS ANGKET KESADARAN KARIER - Azzachra Safira; Heris Hendriana; Wiwin Yuliani (IKIP Siliwangi, 2021)
Career awareness is very necessary to develop the potential that exists in students to help understand, plan and make career decisions of students, because the function of career awareness is very important, a career awareness measurement tool is needed, namely in the form of a career awareness questionnaire that has been tested for validity and reliability . The subjects of this study were 24 students of SMKNPP Cianjur class X totaling 24 students. From the results of the validity test of 30 statements, there were 3 questions that were declared valid and the validity test got a value of 0.400 which means that it is included in the moderate category meaning that the questionnaire that has been compiled tends to show the same results and if it is tested again on time and on other subjects, the results are not far away. different. Keywords: career awareness, validity, reliability.